Investigation of School Effects on Student Achievement in Primary Education Using Value-Added Assessment - Koc, Filiz (Eurasian journal of educational research, 2018)
Purpose: The purpose of this study is to assess the contribution of primary schools within the metropolitan municipality of the province of Ankara, Turkey to the achievement outcomes of 7th grade students using the results of the end of year Level Determination Exam. Research Methods: Carried out using a casual comparative study framework, the population of this study consists of the primary schools in the province of Ankara. The sample includes the 24 primary schools whose students have attended to the same school in both the 2007-2008 and 2008-2009 educational years within the territorial jurisdiction of the metropolitan municipality of the capital of Turkey. The value-added effects of the schools in the sample on the student growth are assessed using a simple fixed-effect model. Moreover, in order to determine whether or not there exists a statistically significant relationship between the rankings of the schools according to average student achievement levels and the rankings according to the value-added effects on student growth, Kendall tau rank correlation coefficients are calculated. Findings: The results of this study indicate that there are significant inconsistencies between the rankings of the schools according to their value-added effects on student improvement and the rankings according to the average student achievement, the latter being the method frequently used to assess the performance of the schools in Turkey. Moreover, the results demonstrate that the value-added effects of the schools on student improvement differ drastically from subject to subject. Implications for Research and Practice: It is expected that this research will lead to a more balanced evaluation of schools particularly given the likely emergence of more data over the years. In addition, this is the first value-added assessment study carried out in Turkey. It points out that the way Turkish schools are assessed is problematic and suggests that value-added methods should be considered in evaluating the effects of schools.